Biologically active supplements: safety, efficacy, market review - A. M. Stepanova; А. N. Plutnitskiy; E. V. Gameeva (Фармакоэкономика, 2025)
In October 2024, the Dietary Supplement Health and Education Act (DSHEA) of the United States celebrated its 30th anniversary, having established a new class of supplementary medical products. Over the 30-year period, the use of dietary supplements in the United States has evolved from a few hundred products primarily consisting of vitamins, minerals, and select herbal extracts to more than 75,000 items. Despite the popularity of biologically active supplements (BAS), their concurrent use alongside conventional prescription medications raises concerns regarding potential drug interactions, particularly among individuals with comorbidities. An increasing number of patients with chronic diseases use BAS; however, a global consensus regarding their safety remains elusive. The present paper reviews the efficacy and safety of BAS, as well as the market for such products. The presented data underscore the risks associated with the global proliferation of BAS, thus necessitating the development of an effective collaboration among consumers, practicing physicians, and government institutions, as well as the establishment of international criteria for assessing the risks of adverse events. This eventually enhances transparency and trust in the products. In order to ensure safety, a stricter regulation and an efficient control system are required to facilitate adequate monitoring and recording of complications that may arise due to the use of BAS.